2012
DOI: 10.1186/1756-0500-5-244
|View full text |Cite
|
Sign up to set email alerts
|

Confocal laser scanning microscopy analysis of S. epidermidis biofilms exposed to farnesol, vancomycin and rifampicin

Abstract: BackgroundStaphylococcus epidermidis is the major bacterial species found in biofilm-related infections on indwelling medical devices. Microbial biofilms are communities of bacteria adhered to a surface and surrounded by an extracellular polymeric matrix. Biofilms have been associated with increased antibiotic tolerance to the immune system. This increased resistance to conventional antibiotic therapy has lead to the search for new antimicrobial therapeutical agents. Farnesol, a quorum-sensing molecule in Cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 44 publications
2
33
0
Order By: Relevance
“…In addition, it has been reported that farnesol is capable of disaggregating bacterial biofilm structure, reducing its biomass (Cerca et al 2012), and allowing the contact of antibiotics with the cells entrapped within the biofilm structure (Katragkou et al 2014). The results of the present research corroborate these findings, since the microscopic analyses of mature B. pseudomallei biofilms revealed that exposure to MBEC concentrations of farnesol promoted disaggregation of the matrix and, consequently, destruction of the biofilm.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, it has been reported that farnesol is capable of disaggregating bacterial biofilm structure, reducing its biomass (Cerca et al 2012), and allowing the contact of antibiotics with the cells entrapped within the biofilm structure (Katragkou et al 2014). The results of the present research corroborate these findings, since the microscopic analyses of mature B. pseudomallei biofilms revealed that exposure to MBEC concentrations of farnesol promoted disaggregation of the matrix and, consequently, destruction of the biofilm.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, it has been reported that farnesol is capable of disaggregating bacterial biofilm structure, reducing its biomass (Cerca et al . ), and allowing the contact of antibiotics with the cells entrapped within the biofilm structure (Katragkou et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…For more detailed analysis of the cleavage specificity, the lists of biochemistry techniques were implemented, such as 1 H NMR spectroscopy, FABMS, MALDI MS, GC MS, ESI-MS, and EIMS (Thurow et al 1974; Linnerborg et al 2001). There is also the possibility to measure biofilm thickness by confocal laser scanning microscopy (CLSM) (Cerca et al 2012), scanning electron microscopy (SEM), or atomic force microscopy (Chatterjee et al 2014). A fully electric tuning fork resonance frequency measurement system designed by Piasecki et al (2015) offered an effective mass measurement in a novel approach to evaluate the bacterial biofilm parameters such as mass, viscosity, and density.…”
Section: Polysaccharide Depolymerasesmentioning
confidence: 99%
“…; Cerca et al . ). Therefore, biofilm‐forming strains could be responsible for the recurrence of urogenital infections (UGI) (Harriott et al .…”
Section: Introductionmentioning
confidence: 97%
“…The micro-organisms included in biofilms show a different behaviour than planktonic cells and thus are more resistant to conventional treatments with antimicrobials, being able to evade the host's immune system more easily (Dales et al 2009;Cerca et al 2012). Therefore, biofilmforming strains could be responsible for the recurrence of urogenital infections (UGI) (Harriott et al 2010;Swidsinski et al 2011).…”
Section: Introductionmentioning
confidence: 99%